Additions to Market Indices and the Comovement of Stock Returns Around the World - Yafeh, Yishay (IMF Working Papers; Working Paper, 2011)
Using newly-constructed data covering the last decade, we document that, in most of forty markets, when added to the main index, firms' returns experience an increase in comovement with the rest of the index, reflected in higher beta and greater explanatory power of the market return. Stock turnover and analyst coverage also typically increase upon inclusion. Using various tests, we find the demand-based view of comovement (the category/habitat theories of Barberis, Shleifer and Wurgler, 2005) to provide a good explanation for many of our findings. Some results, though, suggest that information-related factors are also important in explaining the increased comovement.